2016
DOI: 10.1590/1982-0224-20150039
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of three juvenile mojarras (Gerreidae) in a tropical estuary of northeastern Brazil

Abstract: Distributions and feeding ecology of mojarra species from shallow water of a tropical estuary in Northeastern Brazil were observed aiming to investigate differences in distribution and resource partitioning among juveniles of three species of mojarras. Fishes were collected with a beach seine across four sites along a salinity gradient from January to December of 2011. Highest abundances were recorded during the rainy season in the upper and middle estuary. Microcrustaceans, mainly copepods, were the preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These results were consistent with other studies in Mamanguape estuary to investigate spatial patterns of fish assemblages [ 60 , 73 ]. Similarly, Araújo et al [ 74 ] reported that the mojarra fish species (Gerreidae) used spatial segregation in the use of habitats along the estuarine gradient, while Araújo et al [ 75 ] indicated the environmental variations influencing the distribution of two puffer fish species ( S . testudineus and Colomesus psittacus ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with other studies in Mamanguape estuary to investigate spatial patterns of fish assemblages [ 60 , 73 ]. Similarly, Araújo et al [ 74 ] reported that the mojarra fish species (Gerreidae) used spatial segregation in the use of habitats along the estuarine gradient, while Araújo et al [ 75 ] indicated the environmental variations influencing the distribution of two puffer fish species ( S . testudineus and Colomesus psittacus ).…”
Section: Discussionmentioning
confidence: 99%
“…Competition between species for shared resources generally increases differential resource utilization and decreases niche overlap between species (Amorim et al ., 2016). Sympatric species that interact are theoretically expected to evolve niche separation and resource partitioning to reduce competition (Araújo et al ., 2016). Thus, ecological resource partitioning mechanisms, such as prey and habitat selection and time segregation, minimize competition and allow these species to coexist (Carvalho & Tejerina-Garro, 2014).…”
Section: Introductionmentioning
confidence: 99%